“It’s a Battle for Information”: Mau Mau as the Boogeyman of Decolonization - Biggs, Dylan (Perceptions, 2019)
This paper sought to place a collection of newsreels from Pathé News about the Mau Mau rebellion in Kenya into the historical narrative of the revolt. The current understanding of the Mau Mau has not included a comprehensive discussion of the coverage of the group and the way that news of the revolt shaped the history that follows it. What was observed throughout the reels was an increasingly hostile propaganda campaign against the Mau Mau. This stronger rhetoric coincided with greater atrocities committed by the British as the war dragged on. The main findings of the paper were that the Mau Mau became a kind of “boogeyman” for the British about the dangers of decolonization, as well as the way that the news about the revolt served to paint the revolt in explicitly racist terms. The Mau Mau play an important role in the history of Kenya, and collections like that of Pathé News help to illuminate the narrative that the British developed for the independence struggle.